Pengaruh Stres terhadap Kejadian Migrain - Alfira Aulia (Lembaga Penelitian dan Pengabdian Masyarakat Akademi Keperawatan Sandi Karsa (Merger) Politeknik Sandi Karsa, 2021)
Introduction; Migraine is identified as the cause of primary headache which is characterized by the onset of unilateral pain, as well as accompanying symptoms such as visual disturbances, nausea, and even vomiting. The aim is to conduct a literature study on the effect of stress on migraine incidence. Method; is a literature review by conducting a literature review on articles that are relevant to the research objectives. Result; Stress as a psychological response that arises if there is excessive psychological stress or burden can affect the incidence of migraines. The level of stress is directly proportional to the intensity and frequency of migraines in a person. Conclusion; that doing stress management and stress coping, doing spiritual strengthening, doing relaxation and refreshing on a regular basis and taking advantage of this time to get rid of existing boredom or burdens, utilizing counseling tools.